(Activated Carbon From Coconut Shell Charcoal by â Dry Distillationâ) - G. Pohan, H (Balai Besar Industri Agro, 1988)
Coconut shell charcoal was converted into activated carbon by means of dry distillation method at approximately 600 degree celcius with or witout a very limited amount of oxygen. The activation time used were 1,2, and 3 hours respectively. The samples were then cooled using hot or cold water, with three different colling times of 1,2 and 3 minutes. Parameters taken in the analysis were yield, ash content and iodine adsorption. The results showed that the yield varied from 73,09% to 80,85%. The lowest ash content was 1,99% and the highest iodine adsorption was 700,17 mg/g.